Webinars as the Tutorial at the present stage of Education Development - Kassenova, Aygul; Ogorodnikova A.V., Ogorodnikova A.V. (Рroblems of engineering and professional education, 2023)
The article is devoted to the issue of using Internet technologies in the sphere of education. Especially it concerns distance learning process. Distance learning is naturally integrated into real system of training of a higher educational institution (internal, correspondence, remote), improving and developing it due to creation of the mobile information environment of training, expansion of network of educational structures in Kazakhstan and abroad.